2017
DOI: 10.1021/acs.jnatprod.7b00424
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Vinca minor Leaves with Methyl Jasmonate Extensively Alters the Pattern and Composition of Indole Alkaloids

Abstract: Alkaloids extracted from mature Vinca minor leaves were fractionated by preparative HPLC. By means of HRMS and NMR data, the main alkaloids were identified as vincamine, strictamine, 10-hydroxycathofoline, and vincadifformine. Upon treatment with methyl jasmonate (MeJA), the pattern and composition of the indole alkaloids changed extensively. While 10-hydroxycathofoline and strictamine concentrations remained unaltered, vincamine and vincadifformine levels showed a dramatic reduction. Upon MeJA treatment, four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Notably, the 1 H and 13 C NMR data of the synthetic vincadifformine were identical to that of natural vincadifformine, which are different from those from Andrade's synthesis. We found that this problem could be solved by adding a trace amount of TFA during collection of the NMR spectroscopic data …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the 1 H and 13 C NMR data of the synthetic vincadifformine were identical to that of natural vincadifformine, which are different from those from Andrade's synthesis. We found that this problem could be solved by adding a trace amount of TFA during collection of the NMR spectroscopic data …”
Section: Figurementioning
confidence: 99%
“…We found that this problem could be solved by adding at race amount of TFAd uring collection of the NMR spectroscopic data. [13] In summary,w eh ave achieveda symmetrict otal syntheses of vincadifformine. The key C19 stereogenic center capitalized on ac hiral-cation-directed asymmetric Mannich reaction, which was catalyzed by our recently developed amino acid derived chiral bifunctional thiourea-phosphonium salt.…”
mentioning
confidence: 99%
“…Furthermore, a V. minor counterpart of the C. roseus TPT2 transporter, involved in the secretion of MIAs to the leaf surface, has also been characterized [8] together with a picrinine N-methyltransferase involved in ervincine biosynthesis [11]. At the metabolic level, while the intracellular distribution of MIAs is still a matter of debate in leaves of V. minor [8,12], experimental evidence tends to confirm that MIA metabolism is higher in younger tissues and notably young leaves [13][14][15]. In addition, vincamine has been described as the main alkaloid found in the leaves of V. minor (0.13%) whereas 1,2-dehydroaspidospermidine is the major alkaloid detected in the roots (0.28% [16]).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, vincamine has been described as the main alkaloid found in the leaves of V. minor (0.13%) whereas 1,2-dehydroaspidospermidine is the major alkaloid detected in the roots (0.28% [16]). Finally, some alkaloids are also specific to V. minor leaves, including vincarubine, picrinine, eburnamine, eburnamonine, minovincinine, minovine, vincadifformine and strictamine [7,8,12,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation